Risk factors for recurrent stress fractures in athletes - Korpelainen, R.; Orava, S.; Karpakka, J.; Siira, P.; Hulkko, A. (The American Journal of Sports Medicine, 2001)
Our aim was to identify factors predisposing athletes to multiple stress fractures, with the emphasis on biomechanical factors. Our hypothesis was that certain anatomic factors of the ankle are associated with risk of multiple stress fractures of the lower extremities in athletes. Thirty-one athletes (19 men and 12 women) with at least three separate stress fractures each, and a control group of 15 athletes without fractures completed a questionnaire focusing on putative risk factors for stress fractures, such as nutrition, training history, and hormonal history in women. Bone mineral density was measured by dual-energy x-ray absorptiometry in the lumbar spine and proximal femur. Biomechanical features such as foot structure, pronation and supination of the ankle, dorsiflexion of the ankle, forefoot varus and valgus, leg-length inequality, range of hip rotation, simple and choice reaction times, and balance in standing were measured. There was an average of 3.7 (range, 3 to 6) fractures in each athlete, totaling 114 fractures. The fracture site was the tibia or fibula in 70% of the fractures in men and the foot and ankle in 50% of the fractures in women. Most of the patients were runners (61%); the mean weekly running mileage was 117 km. Biomechanical factors associated with multiple stress fractures were high longitudinal arch of the foot, leg-length inequality, and excessive forefoot varus. Nearly half of the female patients (40%) reported menstrual irregularities. Runners with high weekly training mileage were found to be at risk of recurrent stress fractures of the lower extremities.